2018
DOI: 10.1021/acs.nanolett.8b02123
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Growth Regimes of Hydrothermally Synthesized Potassium Tantalate Nanoparticles

Abstract: A general mathematical kinetic growth model is proposed on the basis of observed growth regimes of hydrothermally synthesized KTaO nanoparticles from electron microscopy studies on the surface morphology and surface chemistry. Secondary electron imaging demonstrated that there are two dominant growth mechanisms: terrace nucleation, where the surfaces are rough, and terrace growth, where surfaces are smooth. In the proposed model based upon standard step-flow growth, the rates of both mechanisms are established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…These values are in agreement with previously reported values , and help explain the large charging: the band gap and work function of DyScO 3 are approximately equal, so almost every secondary electron produced by inelastic scattering in the bulk has sufficient energy to escape the material. As a direct confirmation of this hypothesis, Figure compares secondary electron images of GdScO 3 and KTaO 3 nanoparticles. , As can be seen in this image, the GdScO 3 nanoparticles have less topographic contrast than the KTaO 3 nanoparticles, and a significantly lower secondary electron signal except near the conducting carbon support or KTaO 3 nanoparticles. The lack of topographic contrast directly indicates a long mean free path of the electrons; the lower secondary electron signal is because the GdScO 3 has charged significantly more positive than the KTaO 3.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…These values are in agreement with previously reported values , and help explain the large charging: the band gap and work function of DyScO 3 are approximately equal, so almost every secondary electron produced by inelastic scattering in the bulk has sufficient energy to escape the material. As a direct confirmation of this hypothesis, Figure compares secondary electron images of GdScO 3 and KTaO 3 nanoparticles. , As can be seen in this image, the GdScO 3 nanoparticles have less topographic contrast than the KTaO 3 nanoparticles, and a significantly lower secondary electron signal except near the conducting carbon support or KTaO 3 nanoparticles. The lack of topographic contrast directly indicates a long mean free path of the electrons; the lower secondary electron signal is because the GdScO 3 has charged significantly more positive than the KTaO 3.…”
mentioning
confidence: 54%
“…As a direct confirmation of this hypothesis, Figure 3 compares secondary electron images of GdScO 3 and KTaO 3 nanoparticles. 38,39 As can be seen in this image, the GdScO 3 nanoparticles have less topographic contrast than the KTaO 3 nanoparticles, and a significantly lower secondary electron signal except near the conducting carbon support or KTaO 3 nanoparticles. The lack of topographic contrast directly indicates a long mean free path of the electrons; the lower secondary electron signal is because the GdScO 3 has charged significantly more positive than the KTaO 3.…”
mentioning
confidence: 71%
“…The nanocuboids shown in Figure 2 were typical of particles grown at lower KF/KOH concentrations, and their morphologies matched the nucleation and growth via surface terraces behavior studied previously. 15,16 In contrast to the nanocuboids, anisotropically shaped particles also formed at higher concentrations of KF (KF/KOH > 0.20). These particles were flat rectangular flakes on the order of several hundred nanometers wide and ∼100 nm thick (Figure 3), and EDS maps of these particles shown in Figure S1 did not demonstrate any significant composition segregation as the cuboidal KTN particles did.…”
Section: ■ Resultsmentioning
confidence: 99%
“…SE imaging of REScO 3 (RE = La, Nd, Sm, Gd) particles (Figure 4) confirmed that these conditions led to smaller and better faceted particles, as the GdScO 3 particles produced with the two-step heat treatment (Figure 4) were more faceted than those produced with only a single nucleation step (Figure 2). Increasing the nucleation temperature further would likely increase the nucleation rate and reduce particle size [35]. In addition, the small particulates found in the one-step samples were no longer present in the two-step heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There are advantages to approaching the problem as one of nucleation and growth instead. In a recent analysis of the growth of KTaO 3 nanoparticles [35], it was determined that the growth process could be subdivided into two regimes, one with a high chemical potential difference where terrace nucleation and rough-stepped surfaces dominated, and one with a lower chemical potential difference where step-flow growth annihilated steps to smooth surfaces. This analysis leads to predictions regarding which parameters need to be varied to control the nucleation and growth processes, ultimately tuning the conditions to produce particles with specific shapes or sizes.…”
Section: Introductionmentioning
confidence: 99%